Total joint Perioperative Surgical Home: an observational financial review - Raphael, Darren R (BioMed Central, 2014)
BACKGROUND: The numbers of people requiring total arthroplasty is expected to increase substantially over the next two decades. However, increasing costs and new payment models in the USA have created a sustainability gap. Ad hoc interventions have reported marginal cost reduction, but it has become clear that sustainability lies only in complete restructuring of care delivery. The Perioperative Surgical Home (PSH) model, a patient-centered and physician-led multidisciplinary system of coordinated care, was implemented at UC Irvine Health in 2012 for patients undergoing primary elective total knee arthroplasty (TKA) or total hip arthroplasty (THA). This observational study examines the costs associated with this initiative. METHODS: The direct cost of materials and services (excluding professional fees and implants) for a random index sample following the Total Joint-PSH pathway was used to calculate per diem cost. Cost of orthopedic implants was calculated based on audit-verified direct cost data. Operating room and post-anesthesia care unit time-based costs were calculated for each case and analyzed for variation. Benchmark cost data were obtained from literature search. Data are presented as mean ± SD (coefficient of variation) where possible. RESULTS: Total per diem cost was $10,042 ± 1,305 (13%) for TKA and $9,952 ± 1,294 (13%) for THA. Literature-reported benchmark per diem cost was $17,588 for TKA and $16,267 for THA. Implant cost was $7,482 ± 4,050 (54%) for TKA and $9869 ± 1,549 (16%) for THA. Total hospital cost was $17,894 ± 4,270 (24%) for TKA and $20,281 ± 2,057 (10%) for THA. In-room to incision time cost was $1,263 ± 100 (8%) for TKA and $1,341 ± 145 (11%) for THA. Surgery time cost was $1,558 ± 290 (19%) for TKA and $1,930 ± 374 (19%) for THA. Post-anesthesia care unit time cost was $507 ± 187 (36%) for TKA and $557 ± 302 (54%) for THA. CONCLUSIONS: Direct hospital costs were driven substantially below USA benchmark levels using the Total Joint-PSH pathway. The incremental benefit of each step in the coordinated care pathway is manifested as a lower average length of stay. We identified excessive variation in the cost of implants and post-anesthesia care.